Keanekaragaman Laba-laba Pada Pertanaman Jambu Mete Monokultur dan Polikultur di Lombok Utara - I Wayan Suana; Hery Haryanto (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2010)
Agricultural practice is suspected to influence the availability of spiders in cashew plantation. The aim of this research was to study the diversity of spider in two different agricultural practices: monoculture and polyculture. The research was conducted in cashew plantations in Desa Kayangan (monoculture) and Desa Salut (polyculture), Lombok Utara. Two trapping techniques were used to sample the spiders: sweep net and pitfall trap. In each study area, 10 sampling sites were selected along line transect that was 5000 meters long. The study found 36 species of spiders from 12 families. The diversity and richness of spiders were higher in the polyculture cashew plantation than that in monoculture. Habitat structure was more complex in the polyculture cashew plantation; hence many species of spiders were able to coexist there.